2018
DOI: 10.3390/w10111551
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Comparative Study on the Flow-Induced Vibration of a Plane Gate

Abstract: A numerical method is applied here to simulate the unstable flow and the vibration of a plane gate. A combination of the large eddy simulation (LES) method and the volume of fluid (VOF) model is used to predict the three-dimensional flow field in the vicinity of a plane gate with submerged discharge. The water surface profile, the streamline diagrams, the distribution of turbulent kinetic energy, the power spectrum density curve of the fluctuating pressure coefficient at typical points underneath the gate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…As it was obtained previously in articles [17][18][19], the vibration impact of an oscillating wall to the flow leads to a change of the particle velocity by a periodic law, which is a superposition of several components.…”
Section: Research Methodology 21 Previous Approximation Of the Basssupporting
confidence: 62%
See 1 more Smart Citation
“…As it was obtained previously in articles [17][18][19], the vibration impact of an oscillating wall to the flow leads to a change of the particle velocity by a periodic law, which is a superposition of several components.…”
Section: Research Methodology 21 Previous Approximation Of the Basssupporting
confidence: 62%
“…where c(t), ψ(t) -dimensionless time and phase functions, respectively, which are determined by comparing the expressions (15) and (18):…”
Section: Clarification Of the Complementary Functionsmentioning
confidence: 99%
“…At last, the emergency gate is completely closed and the flow cuts off. Shen et al [23] established the fluid-structure interaction numerical simulation for the emergency gate through Fluent and studied the gate vibration in a fixed gate opening. They believed that turbulent pressure and multi-vortex mixing were the main reasons for the gate flow-induced vibration.…”
Section: Flow Field Distributionmentioning
confidence: 99%
“…Ng CF et al [19] studied the effect of radial gate elevation on the loading of the gate wall under the action of water flow, and they obtained numerical results similar to the experimental results by using the numerical simulation and experimental comparison of the three-dimensional model of the shrinkage dam. Shen C et al [20] carried out numerical simulation and field prototype observation on a plane gate and found that the numerical simulation's results were not much different from the prototype observation results. In summary, many researchers have studied the structural calculation of the gate, mainly using the combination of model tests and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%